1983
DOI: 10.1007/bf00695054
|View full text |Cite
|
Sign up to set email alerts
|

The scarring of the liver acini (Cirrhosis)

Abstract: Cirrhosis is defined as the scarring of the liver acini in zone 3, zone 1 or in both; the resulting nodules are scarred and modified remnants of acini of various orders. The division of the nodules into "micronodules" and "macronodules" is difficult to justify as their two dimensional appearance changes at different planes of section. Early scar formation precedes changes in the microcirculatory dynamics. Sprouting of vascular branches, especially of arterioles, takes the leading role in the development of mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…Similar interfaces are observed between regenerative nodules and surrounding tissues in cirrhosis (24). The formation of active fibrous septa may thus represent the LCTC populations spreading and migrating along discontinuous interfaces of extracellular matrix.…”
Section: Resultsmentioning
confidence: 57%
“…Similar interfaces are observed between regenerative nodules and surrounding tissues in cirrhosis (24). The formation of active fibrous septa may thus represent the LCTC populations spreading and migrating along discontinuous interfaces of extracellular matrix.…”
Section: Resultsmentioning
confidence: 57%
“…Oxidative stress may stimulate both the accumulation of collagen and extracellular matrix deposition (Kroy et al 2014). Rappaport et al (1983) reported that liver injuries induced changes in microcirculation that were associated with collagen deposition and consequently fibrosis. Acute pancreatitis is considered as high risk factor for vascular disorders (Björk and Arfors 1982).…”
Section: Discussionmentioning
confidence: 99%
“…The proliferated Schwann cells seemed to form a scaffold guiding regenerating nerve fibers [19]. Considering that the noradrenergic fibers run along blood vessels, changes in vascular patterns may also alter hepatic innervation patterns [19,20]. Moreover, scar formation, with changes in the microcirculatory dynamics could influence nerve regeneration [20], and changes in vascularity and inflammation can affect nerve expression [19,21].…”
Section: Discussionmentioning
confidence: 99%